Evolution of self-care dependent individuals admitted to the National Network for Integrated Continuous Care - Petronilho, Fernando (2017)
Background: The National Network for Integrated Continuous Care (NNICC) emerged as a response to the increasing aging of the Portuguese population and the consequent increase in the number of self-care dependent individuals. Objectives: To assess the potential for the recovery of autonomy, the evolution of bodily processes impairment, and the level of self-care dependence among dependent individuals admitted to the NNICC. Methodology: A descriptive and exploratory study was conducted using a convenience sample of 891 dependent individuals from 10 NNICC care units within the area of influence of a Local Coordination Team in the region of Minho, Portugal. Results: The results showed a low to moderate potential for the recovery of autonomy. There was a positive evolution in bodily processes impairment and in the level of self-care dependence. The greater potential for the recovery of autonomy is associated with a lower level of bodily processes impairment and a higher self-care independence. Conclusion: The study reveals effective health gains in the health condition of dependent individuals admitted to the NNICC, within its different types of care, which demonstrates its usefulness.